Centrosome aberrations in bone marrow cells from patients with myelodysplastic syndromes correlate with chromosomal instability - Nolte, Florian; Giehl, Michelle; Prinzhorn, Wiltrud; Nowak, Verena; Schumann, Christiane; Nowak, Daniel; Mossner, Maximilian; Popp, Henning; Schulze, Torsten; Klein, Stefan; Seifarth, Wolfgang; Hofmann, Wolf-Karsten; et al. (Annals of hematology, 2013)
Centrosomes play important roles in the maintenance of genetic stability and centrosomal aberrations are a hallmark of cancer. Deregulation of centriole duplication leads to supernumerary centrosomes, sister chromatid missegregation and could result in chromosomal instability (CIN) and aneuploidy. CIN is a common feature in at least 45 % of patients with myelodysplastic syndromes (MDS). Therefore, we sought to investigate the centrosomal status and its role for development of CIN in bone marrow (BM) cells of MDS patients. BM cells of 34 MDS patients were examined cytogenetically. Furthermore, cells were immunostained with a centrosome-specific antibody to pericentrin to analyze the centrosomal status. Umbilical cord blood specimens and BM cells of healthy persons (n = 11 and n = 4) served as controls. In addition, the protein expression of the protease separase responsible for genetic stability was examined by western blot analysis. Centrosome abnormalities were detected in 10 % (range, 4-17 %) of cells of MDS samples, but in only 2 % (range, 0-4 %) of cells of healthy controls. Normal karyotypes were found in control cells and in BM cells of 16/34 MDS patients. The incidence of centrosomal alterations was higher in BM cells of patients with cytogenetic alterations (mean, 12 %) compared to BM cells of patients without cytogenetic changes (mean, 7 %). Our results indicate that centrosome alterations are a common and early detectable feature in MDS patients and may contribute to the acquisition of chromosomal aberrations. We assume that centrosome defects could be involved in disease progression and may serve as a future prognostic marker.
Gesehen am 26.01.2022